Applying Duolingo as English Learning Media: How do Students Perceive it? - Dewi Yana (INTERNATIONAL JOURNAL OF LANGUAGE PEDAGOGY, 2021)
The advancement of digital technology today has boosted opportunities for teachers to apply digital products in promoting teaching and encouraging the learning process. Knowing how students perceive the use of digital technology is playing a significant role in supporting the achievement of an accommodating learning environment for students. This study is intended to investigate the students' perception of Duolingo as an English learning medium. It belongs to qualitative descriptive research. The data were gathered from an online questionnaire and interview and then analyzed descriptively. The result demonstrates students perceived positively toward applying Duolingo Application as a tool to facilitate English language learning at Senior High school it is interesting, motivating, helpful, encourages students' confidence, and is compatible across Junior High school to University students. However, students also perceived it’s weakness, it is too colorful and words repetition.